The Restructuring of the Venezuelan State and State Theory - Llambi, Luis; Gouveia, Lourdes (The International Journal of Sociology of Agriculture and Food, 2021)
A central objective of this article is to examine the restructuring of the state apparatuses and decision-making processes of economically 'small' and politically 'weak' nation-states as they adjust to the emerging global economic and social order. We focus most specifically on the impact of the above-mentioned projects on two different state restructuring projects - one 'endogenous' the other 'exogenous' - of the Venezuelan Ministry of Agriculture (MAC) and related agencies.?In our analysis, we find that the reorganization of state systems is determined both by structural forces - a particular 'logic of capital' - and by conjunctural factors and contingencies such as the particular balance of social forces and institutional structure present at each juncture. Transnational forces enhance the complex determinacy of state power and autonomy, but their effect is far from clear at this point. We conclude that globalization theory may have been too quick in its generalizations about the current and future fate of the nation-state. The restructuring of current state forms is a highly heterogeneous and contingent process, suggesting the need for a substantial dialog between additional research and formulation of state theory.